Integrasi Pendidikan Karakter dengan Kurikulum Merdeka: Strategi Mengatasi Tantangan Bullying di Sekolah - Asep Khairul Faizin; Chika Ghianistika; Meilia Prehartanti; Sujono; Deden Deni Mahendra (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The increasingly dynamic development of education raises various challenges, one of which is the problem of bullying in schools. Character education is a solution that is considered effective for overcoming this problem, especially if it is integrated into the Independent Curriculum. This research aims to analyze the effect of integrating character education in the Merdeka Curriculum on reducing bullying cases at SDIT Kasih Ibu. This research uses a quantitative design with a quasi-experimental approach, where data is collected through observation, interviews and surveys with students and teachers. The data analysis techniques used are descriptive and inferential statistics to measure changes that occur before and after implementing the character education program. The research results show that the integration of character education has succeeded in reducing the number of bullying in the school from 20% to 5%, especially physical and verbal bullying. The implication of this research is the importance of implementing character education systematically in the school curriculum to create a safer learning environment and support students' social-emotional development. Apart from that, increasing teacher capacity in implementing character education needs attention so that the success of this program can be maintained. This research contributes to the development of educational policies that are more holistic and have a positive impact on the school environment.